Climate Mitigation Policy in Denmark: A Prototype for Other Countries - Nicoletta Batini; Ian Parry; Philippe Wingender (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Denmark has a highly ambitious goal of reducing greenhouse gas emissions 70 percent below 1990 levels by 2030. While there is general agreement that carbon pricing should be the centerpiece of Denmark's mitigation strategy, pricing needs to be effective, address equity and leakage concerns, and be reinforced by additional measures at the sectoral level. The strategy Denmark develops can be a good prototype for others to follow. This paper discusses mechanisms to scale up domestic carbon pricing, compensate households, and possibly combine pricing with a border carbon adjustment. It also recommends the use of revenue-neutral feebate schemes to strengthen mitigation incentives, particularly for transportation and agriculture, fisheries and forestry, though these schemes could also be applied more widely.
Keywords: Q48; Q54; Q58; H23; 330; climate change; Denmark climate mitigation; carbon pricing; feebate; revenue recycling; border carbon adjustment; transportation; agriculture